Investigating the suitability and cost-benefit of copper tailings as partial replacement of sand in concrete in Zambia: an exploratory study. Issue 4 (6th October 2020) - Muleya, Franco; Mulenga, Bodwin; Zulu, Sambo Lyson; Nwaubani, Sunday; Tembo, Chipozya Kosta; Mushota, Henry
Abstract : Purpose: This study aimed to investigate the suitability and cost-benefit of using copper tailings as partial replacement of sand in concrete production. The study was motivated by the accumulation and non-use of copper tailings in dams among them tailing dam 25 also known as TD 25 in Kitwe city of the Copperbelt province in Zambia that take up approximately 111 hectares of unused land. Design/methodology/approach: Laboratory experimental approach of concrete production based on water/cement ratios of 0.3 and 0.5 was used because this was an exploratory study designed to establish the primary performance of concrete. In total, 30 concrete cubes were cast based on the two water-cement ratios. In total, 0% to 30% partial sand replacement with copper tailings was used in both mixes with the 0% copper tailings replacement being the control mix and reference point. Other concrete tests included workability, density, compressive strength and element composition analysis. Findings: Results revealed that copper tailings from TD 25 were suitable for partial replacement of sand in concrete. Thirty per cent of sand replacement with copper tailings was established as the maximum replacement amount to produce optimum compressive strength values from both mixes. The drier mix of 0.3 water-cement ratios produced higher compressive strength results of 23 MPa at 28 days of concrete curing with 2.34% as optimum concrete cost reduction. Practical implications: The research results provide the cost-benefit analysis and savings that can be attained from using cheaper copper tailings based concrete. The study further provided the quantity of land available for development arising from absorption of copper tailings as a sustainable construction material. The local authority now has statistics and numerical values that it can use to absorb copper tailings as a concrete raw material. Originality/value: The study provides guidance on optimum concrete grade produced and cost reduction details of copper tailing-based concrete to support for local authorities in suitable land wand waste management using real data.